2021
DOI: 10.1099/jgv.0.001473
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel lineage of Crimean–Congo haemorrhagic fever virus in dromedary camels, United Arab Emirates

Abstract: Crimean–Congo haemorrhagic fever virus (CCHFV) is a tick-borne virus causing Crimean–Congo haemorrhagic fever (CCHF), a disease reported to have a high fatality rate in numerous countries. The virus is geographically widespread due to its vector, and numerous wild and domestic animals can develop asymptomatic infection. Serological and limited molecular evidence of CCHFV has previously been reported in Camelus dromedarius (the dromedary, or one-humped camel) in the United Arab Emirates (UAE). In this study, 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 19 publications
4
15
0
Order By: Relevance
“…Another report confirmed the isolation of CCHFV on cell culture from ticks collected from imported animals and showed fatal effects on experimental animals [ 5 ]. The virus detected in this study showed high similarity (96.88–99.67 to the CCHFV strains identified from samples collected from camels, suggesting that camels could be a potential reservoir of CCHFV [ 11 ]. In this study, yet another nairovirus, TOV, was identified for the first time in the Arabian Peninsula.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another report confirmed the isolation of CCHFV on cell culture from ticks collected from imported animals and showed fatal effects on experimental animals [ 5 ]. The virus detected in this study showed high similarity (96.88–99.67 to the CCHFV strains identified from samples collected from camels, suggesting that camels could be a potential reservoir of CCHFV [ 11 ]. In this study, yet another nairovirus, TOV, was identified for the first time in the Arabian Peninsula.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, camels have been associated with the transmission of several viral diseases to humans. KADV, AHFV, CCHFV, Tamdy virus (TOV) and MERS are associated with camels [ 3 , 11 , 12 , 13 ]. For instance, Hemida et al found that 90% of camel populations were MERS-CoV seropositive [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, CCHFV with the Africa lineage M segment has never been found outside Africa except for Spain [ 29 ]. In addition, there are no reports of African CCHFV with the Asian-origin S or L segment, whereas the viruses with the African-origin S segment have been detected in Russia and United Arab Emirates [ 30 ]. The mechanism underlying the high frequency of M segment reassortment compared to the S and L segments is totally unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the cases involved workers of livestock markets, butchers, and animal skin processors [ 54 , 55 ]. Recently, a novel lineage of CCHFV was detected in dromedary camels ( Camelus dromedarius ) and camel ticks ( Hyalomma dromedarii ) with potential reassortment of the M segment of the genome [ 56 , 57 , 58 ].…”
Section: Worldwide Burden and Phylogenetics Of Cchfvmentioning
confidence: 99%